The Influence of Corporate Social Responsibility (CSR) and Profitability on Firm Value - Irma Wati; Melisa Sinaga; Rika Kartikasari; Wasniyah Wasniyah; Ani Kusumaningsih (The Future of Education Journal, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) and profitability on firm value in mining sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research uses a quantitative approach with secondary data obtained from annual reports, financial statements, and sustainability reports. The sampling technique used is purposive sampling, resulting in 30 observations. Data analysis was conducted using panel data regression with the Random Effect Model (REM) as the selected model. The results show that partially, Corporate Social Responsibility (CSR) does not have a significant effect on firm value, while profitability has a significant positive effect on firm value. Simultaneously, CSR and profitability have a significant effect on firm value. The coefficient of determination indicates that the independent variables explain 26.73% of the variation in firm value, while the remaining 73.27% is influenced by other variables outside the model. These findings suggest that profitability plays a more important role in influencing firm value compared to CSR in the mining sector.